The evolutionary logoi: a constructive theological engagement of Maximus the Confessor with evolutionary biology - Jackson, Andrew P. (2023)
This thesis brings Maximus the Confessor’s logoi doctrine into dialogue with modern-day evolutionary biology. Motivated by a number of recent scientific allusions to the logoi, it first explores the extent to which the logoi, as described by Maximus, exhibit features that are concordant with evolution before going on to consider more discordant aspects that cannot be ignored. Based on an interpretation of the logoi as constitutively immanent formal principles that appear in time and expand and contract interactively, the case is made that the logoi do indeed bear a strong resemblance to the phylogenetic unity-in-difference that is the hallmark of Darwinian descent with modification. Not only are the logoi evolutionary in our physically-observable spacetime but they also could be said to evolve metaphysically from their timeless intentionality in God to their final consummation in the Logos. As to their more disanalogous features: some of these, such as their immutability, purposefulness and determinative character, can be shown to be only superficially at odds with biological evolution, while their goodness (as the very Logos) poses greater challenges. However, by drawing upon further resources from Maximus and the Eastern tradition, it is argued, more speculatively, that the underlying goodness of the logoi can still be seen in certain elements of the Darwinian process while other elements correspond to the so-called ‘garments of skin’ imposed by God as part of a simultaneous creation and fall. Overall, this study joins with other Maximian interpreters in attesting to the incarnational and theophanic nature of the logoi, but seeks to extend this distinctively Eastern Christo-cosmology into the problematic territory of biological evolution, a territory historically dominated by Western scholarship.